2015
DOI: 10.15698/mic2015.10.231
|View full text |Cite
|
Sign up to set email alerts
|

Formyl-methionine as a degradation signal at the N-termini of bacterial proteins

Abstract: In bacteria, all nascent proteins bear the pretranslationally formed N-terminal formyl-methionine (fMet) residue. The fMet residue is cotranslationally deformylated by a ribosome-associated deformylase. The formylation of N-terminal Met in bacterial proteins is not strictly essential for either translation or cell viability. Moreover, protein synthesis by the cytosolic ribosomes of eukaryotes does not involve the formylation of N-terminal Met. What, then, is the main biological function of this metabolically c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 131 publications
2
71
0
Order By: Relevance
“…1 and 2 and SI Appendix, Fig. S2A) (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Other studies, in the 1990s and afterward, have also identified many internal degrons, defined as degradation signals whose functionally essential elements do not include either Nt-residues or C-terminal (Ct) residues.…”
Section: Terminology For Proteolytic Pathways That Target N-termini Amentioning
confidence: 99%
“…1 and 2 and SI Appendix, Fig. S2A) (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Other studies, in the 1990s and afterward, have also identified many internal degrons, defined as degradation signals whose functionally essential elements do not include either Nt-residues or C-terminal (Ct) residues.…”
Section: Terminology For Proteolytic Pathways That Target N-termini Amentioning
confidence: 99%
“…In contrast to nuclear‐derived proteins, plastid‐encoded proteins initiate with Nt‐fMet, and undergo cotranslational deformylation followed by Nt‐Met excision, which are both essential for normal plastid development (Giglione et al ., ; van Wijk, ). Interestingly Met‐retention on chloroplast proteins has previously been linked to protein instability (Giglione et al ., ), whilst fMet can act as a destabilizing residue in bacteria, and possibly also chloroplasts (Piatkov et al ., ). Cotranslational and posttranslational Nt‐acetylation also occurs on chloroplastic proteins, which appears to enhance protein stability (Bienvenut et al ., ); recently a nuclear‐encoded chloroplast‐targeted NAT that probably catalyses this modification has been identified (Dinh et al ., ).…”
Section: The N‐terminus As a Stability Determinant In Plastidsmentioning
confidence: 99%
“…1) (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). The main determinant of an N-degron is a destabilizing Nt-residue of a protein.…”
mentioning
confidence: 99%